(5, 1)
7(3y-2)-(-4y+9)
If you mean: 2x-3y = 7 then y = 2/3x-7/3 whereas 2/3 is the slope and -7/3 is the y intercept of the straight line.
5x + 3y = -7x = 43 - 8y5x + 3y = -75(43 - 8y) + 3y = -7215 - 40y + 3y = -7215 - 37y = -7215 -215 -37y = -7 - 215-37y = -222-37y/-37 = -222/-37y = 6x = 43 - 8yx = 43 - 8(6)x = 43 - 48x = -5Thus, (-5, 6) is the solution of the given system of the linear equations.
The ordered triple is (x, y, z) = (1, -1, -2)
2
x=2 y=7 5x+3y= 5 7 x 2 x 3 ____ _____ 10 21 21 + 10 _______ 31
5 - 2y = -3y - 2Subtract 5 from each side:-2y = -3y - 7Add 3y to each side:y = -7
are you talking about a system of equations where x+3y=-7 -x+2y=-8 if so, then the answer is {2,-3}
2(7)=3(7) 14=21
7x+3y where x=2 and y=9 can be written as (7*2)+(3*9) which can be simplified to (14)+(27), from there it's basic addition.
Stating that it is an equilateral triangle, we are told that all sides are equal.This is another way of saying:4x - y = 7and2x + 3y = 7So this can be solved by eliminating one of those variables:2x + 3y = 7x = (7 - 3y) / 24((7 - 3y) / 2) - y = 714 - 7y = 7y = 1x = 2
5y+14+y = 3y-7 5y+y-3y = -7-14 3y = -21 y = -7
given is that 4x+3y=6(3x+3y)=7 i.e., 6(3x+3y)=7 &&& 4x+3y=7 ---------------(1) 3x+3y=7/6 x+y=7/18 _________(2) multiply eqn(2) by 4 4x+4y=28/18 -------------------------(3) (3)-(1) 4x+3y-4x-4y=7-(28/18) y= -98/18 substitute y in eqn(2) x-98/18=7/18 x=7/18+98/18 x=105/18. therefore x=105/18 : y= -98/18
Since 2x-3y=4y=8 we can say that 4y=8 therefor y=2 We can also say that 2x-3y=4y and as y=2 2x-6=8 so 2x=14 and x =7 so y=2 and x=7
7 + 8y - 3y + 2 =7 + 2 + 8y - 3y = 9 + 8y - 3y = 9 + 5y
y=5